Lemmus lemmus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
31. Norway Brown Lemming Lemmus lemmus French: Lemming de Norvege / German: Berglemming / Spanish: Lemming de Noruega Other common names: Norway Lemming, Norwegian Lemming Taxonomy. Mus lemmus Linnaeus, 1758, Lappmark, Sweden. Lemmus lemmus is closely related to L. sibiricus. The two lemmings easily hybridize under laboratory conditions. Recent phylogeographic analysis showed that L. lemmus did not colonize its current distribution from the south but survived the Last Glacial Maximum in an ice-free Fennoscandian refugium. Monotypic. Distribution. Endemic to Fennoscandia, specifically to the Scandinavian Peninsula (Norway and N & W Sweden), N Finland, and Kola Peninsula (NW Russia); S border fluctuates ¢.200 km, shifting S during cyclic peaks. Descriptive notes. Head-body 112-150 mm, tail 10-18 mm; weight 40-130 g. The Norway Brown Lemming is chunky, with relatively large, broad, and flattened head; small eyes; and short, tufted ears. Tail is slightly shorter than hindfoot, densely haired with long ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 293, DOI: 10.5281/zenodo.6707142 ...